Research on multi-dimensional iOS privacy disclosure evaluation model - Yue-xiu XING; Ai-qun HU; Yong-jian WANG; Ran ZHAO (网络与信息安全学报)
The existing iOS platform is lacking ofsystematic assessment methods of privacy leak detection.To solve this problem,a multi-dimensional iOSprivacy disclosure evaluation model was presented.This model combined static analysis,dynamic analysis and network data analysis method to extract the features of the application’s pri-vacy disclosure behavior and evaluate it form multiple dimensions way.The model on 30 different types of apps from the iOS App Store and found out that more than 50% of all investigated apps aretracking users’ locations were evaluated,almost 40% of all send data to a server without the user’s consent.The model makes up for the limitations of single static analysis or dynamic analysis methods,solves the quantization problem of privacy disclosure effectively.